Institutions of higher education and the idea of lifelong learning - Marcinkiewicz, Aleksandra (Journal of Education Culture and Society, 2020)
The idea of lifelong learning is very popular in the XXI century. This paper presents how Polish universities reflect this idea. The main theories of andragogy were compared with each other and a relationship was shown, between this concept and adult education. Moreover, it analyses the effectiveness of different management styles continuing education in Polish universities and their implications for institutions of higher education. It also describes the main programs of the European Commission to promote lifelong learning in Europe.